Management of the School Literacy Movement through the “KLIMIS” Literacy Program at Kembangan Utara 04 Public Elementary School - Alfin Yansyah; Madhakomala Madhakomala; Muhammad Fadholi (Universitas Negeri Surabaya, 2025)
This study aims to describe the implementation of the School Literacy Movement through the KLIMIS Literacy Program at SDN Kembangan Utara 04. Using a qualitative descriptive approach with observation, interviews, and documentation, the study found that the program was initiated to address students’ low reading ability and school literacy performance. The program was implemented systematically through daily literacy activities and weekly core sessions, supported by school leaders, teachers, librarians, parents, and the mobile library. Evaluation results showed a significant improvement in students’ reading ability and interest from 40% to 70% fluent readers. Challenges such as limited book collections and digital distractions were mitigated through collaboration and digital literacy initiatives. The KLIMIS Program has proven effective in fostering a sustainable reading culture and improving students’ learning outcomes.